Real-world use of empaglifozin and dapaglifozin in patients with HEART failure - Kocabas, U. Uumut; Yavuz, V.; Altin, C.; Kaplan, M.; Oztekin, G. M. Yilmaz; Dogdus, M.; Ozcalik, E. (Wiley, 2024)
[Abstract Not Available]